A fractional Landweber method for solving backward time-fractional diffusion problem. (1st July 2019) - Han, Yaozong; Xiong, Xiangtuan; Xue, Xuemin
Abstract: In this paper, we propose a fractional Landweber regularization method for solving a backward time-fractional diffusion problem. Choice rules for both a-priori and a-posterior regularization parameters are discussed in deriving the corresponding convergence proofs for the backward problem. For verification on the theoretical estimates, several numerical examples are constructed and compared with some existing works.